Great characters’ childhood as Beacon: contents and values in children’s books as cultural references - Sanchidrián-Blanco, María del Carmen (My University, 2015)
Intercultural education, understood as a progressive approach to transform education and to respond to discriminatory policies and practices in education, is by definition contrary to the concept of education in the nacional-catolicismo (1940s to 1960s in Spain), where the main educational goal was to underline the superiority of everything “Spanish”: Spanish people, Spanish food, Spanish language and Spanish religion, of course. Everything "Spanish" was idealized and regarded as superior. This monocultural perspective was taught both directly -by conveying it to to the children and making them repeat and assume- or indirectly. In this paper some examples of the first method taken from the children’s book El hermano de Paloma (Paloma’s Brother) will be analyzed. The second perspective is more complex and it often implies the negation of the multicultural fact and, from this perspective, the cultural differences were hidden and blurred, and, consequently, they were not allowed to be seen. This paper focuses on one of the collections of children’s books published by the Editorial Cervantes: Cuando los grandes santos, reyes, reinas, hombres, mujeres...eran niños (When the great saints, kings, queens, men, women… were children). This collection of 25 volumes, each one between 120 and 150 pages in length, was published and printed in Barcelona, from 1953 to 1962 and it was quite popular; actually, some of the titles were edited several times. Vicente Clavel’s work in Editorial Cervantes needs to be recognized, too. This publisher, writer and translator, is well known for his initiative to establish a Book Day in Spain starting in 1922. Each volume included from eight to ten characters that were used to describe childhood. This kind of books is the perfect frame to present different cultures over time and in different spaces. For example, the volume about the Great female teachers goes from Catherina of Alexandria to Gabriela Mistral, from Egypt to Chile and from the year 287 to 1889. Since one of the sub-themes of this conference deals with the use of myths and stories about people conveying a message about what is valued in each culture, some titles of this collection will be analyzed from this perspective. Do they show different cultures? How are these cultures explained? Which values are promoted? Our main hypothesis is that the cultural differences over time and the different spaces are blurred and that all the characters are described and explained from the same perspective without taking into account the obvious cultural differences. Furthermore, as each title was targeted either to boys or to girls, who were about nine or ten years old, we also study the different values transmitted to boys and girls. Finally, the paper concludes that these issues can be seen as signs of the prevailing culture in Spain in those years.
Keywords: Libros infantiles y juveniles; Educación - España - Historia; History of Education; Material culture; Biographies; Culture and Education; Children's Books